Triplet CFTR modulators: future prospects for treatment of cystic fibrosis - Chaudary N (Dove Medical Press, 2018)
Nauman Chaudary Division of Pulmonary Disease and Critical Care Medicine, Department of Medicine, Virginia Commonwealth University, Richmond, VA, USA Abstract: Cystic fibrosis (CF) is an autosomal recessive genetic disease characterized by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR). CFTR is a chloride channel responsible for ion flow across epithelial surfaces of lung, sinuses, pancreas, intestine, and liver. Researchers have grouped CFTR genetic mutations into various protein defects: reduced protein synthesis (class 1 mutations), abnormal protein folding and maturation (class 2 mutation), and abnormal gating (class 3 mutation). These mutations usually present as severe forms of CF due to complete absence of CFTR at cell surfaces. Milder forms (eg, protein maturation and conductance defects, classes 4–6) present as less severe forms of CF related to the presence of CFTR at the cell surface. Differences in severity are directly due to CFTR function which is based on the severity of CFTR mutation. This knowledge has proven useful for designing therapy for individual mutations and mutation classes. The discovery and US Food and Drug Administration approval of Kalydeco® (ivacaftor) in early 2011 marked the beginning of a new era of therapies that are focused on improving defective CFTR protein function. However, due to its specificity for the G551D mutation, ivacaftor only benefits ~5% of CF patients. Approximately 50% of CF patients have two copies of the F508Del mutation, while other CF patients carry only one copy of this gene. More recently, Orkambi®, a two compound medication composed of lumacaftor and ivacaftor, has provided the foundation necessary to further build on molecular concepts of: correction of trafficking, potentiation, and amplification of defective CFTR. These new concepts will form the basis of future CF therapies and extend CFTR treatment to almost 50% of CF patients. Evolving knowledge of the molecular mechanisms responsible for defective CFTR has prompted new research focused on “repair” of each phase of CFTR expression and function, thus creating a new class of combination “CFTR correctors” referred to as “triplet CFTR compounds.” This article will review how patients can be selected and treated with these newer agents that are based on specific mutations. In the future, many CF practitioners have expectations that initiation of treatment for CF patients will occur simply by use of biomarkers of CFTR expression (eg, sweat chloride, nasal potential difference, rectal organoids) rather than testing for specific mutations. As continued research identifies biomarkers with greater specificity and which predict clinical response, therapies can potentially be tailored to individual responses. Keywords: adults, cystic fibrosis, treatment, CFTR modulators